(untitled) (Fiep Bulletin - online, 2013)
The study seeks to present a structure model to the handball performance of the State Champion Team of Female Handball of Mato Grosso do Sul, with the objective to carry out anthropometric analysis. Twelve athletes were measured at the average of 16 (ID), 16,5 years old; weight (PE) 68,5 kg; hight (ES) 1,70 m; arm span (ENV) 1,72 m; hand breadth (DPA) 18,8 cm; lower limbs length (CMI) 71 cm; body mass index (IMC) 22,8 kg/m²; fat percentage (%G) 23,6%; body fat (MG) 15 kg; lean body mass (MCM) 50,7 kg and ideal weight (PI) 67,6 kg. Glaner (1996) assures that the backcourts and wingers are the game position which are more differentiated between them, and the pivots and backcourts tend to be the tallest athletes, and the wingers of less height. When comparing the athletes by game position, it was noticed that the backcourt and the pivots were the ones who most distanced morphologically between them. What most delimited the study were the little information and little research on female handball. The majority of the searched articles bring information on the variable: height, arm span, hand breadth and lower limbs length, lean and fat body mass and body fat percentage of male handball, making difficult to compare for the discussion of the data analysis. For a better performance in female handball in Mato Grosso do Sul, it is necessary that the technicians take into consideration the morphologic profile of each athlete and analyze in which position they fit better. And may this research stimulate more professionals in the field to carry out scientific works with female handball.